Discovery of a supercluster in the Zone of Avoidance in Vela. (8th November 2016) - Kraan-Korteweg, Renée C.; Cluver, Michelle E.; Bilicki, Maciej; Jarrett, Thomas H.; Colless, Matthew; Elagali, Ahmed; Böhringer, Hans; Chon, Gayoung
Abstract: We report the discovery of a potentially major supercluster that extends across the Galactic plane in the constellation of Vela, at a mean recessional velocity of ∼18 000 km s −1 . Recent multiobject spectroscopic observations of this Vela supercluster (VSCL), using AAOmega+2dF and the Southern African Large Telescope, confirm an extended galaxy overdensity in the Zone of Avoidance (ZOA) located where residual bulk flows predict a considerable mass excess. We present a preliminary analysis of ∼4500 new spectroscopic galaxy redshifts obtained in the ZOA centred on the Vela region (l = 272^°_.5 ± 20^°, b = 0^° ± 10^° ). The presently sparsely sampled data set traces an overdensity that covers 25^° in Galactic longitude on either side of the Galactic plane, suggesting an extent of 25 × 20 deg 2, corresponding to ∼ 115 × 90 h 70 Mpc at the supercluster redshift. In redshift space, the overdensity appears to consist of two merging wall-like structures, interspersed with clusters and groups. Both the velocity histogram and the morphology of the multibranching wall structure are consistent with a supercluster classification. K_s^o galaxy counts show an enhancement of ∼1.2 over the survey area for galaxies brighter than M_K^* at the VSCL distance, and a galaxy overdensity of δ = 0.50–0.77 within a photometric redshift shell around the VSCL, when compared with various Two Micron All-Sky Survey samples. Taking account of selection effects, the VSCL is estimated to contribute v_LG 50 km s −1 to the motion of the Local Group.